Investigating Business Intelligence as a Possible Differentiator for Administrative Competitive Edge - Kutumela, Khomotjo Jane; Lubbe, Sam; Ohei, Kenneth Nwanua (International Review of Management and Marketing, 2022)
Business Intelligence (BI) has been recognised as a crucial component of the organisation’s success. Whilst some organisations are able to exploit and realise the benefits of BI, there are still several organisations that fail to capitalise on its potential. The aim was to investigate BI as a possible differentiator for administrative competitive edge. The study applied a deductive research approach and a quantitative research method. Data was collected using questionnaires from a population of 302 respondents. Results revealed that, the use of BI in organisation is dependent on the employees realising the strong correlation between business alignment, BI and strategy. Management support was found to be a key indicator in demonstrating leadership, commitment, and advocacy towards BI initiatives. The study found that the alignment of BI with strategy within an organisation makes it possible for the organisation to reap the benefits of BI which led to better decision making. BI was found to be useful in assisting respondents to perform and complete their tasks quicker and with ease. The conceptual framework tested in the study comprised of three constructs: strategy alignment, management support and BI utilisation as contributing components in making it a differentiator in gaining a competitive advantage.